EFEKTIVITAS PENERAPAN ICE BREAKING TERHADAP MOTIVASI BELAJAR SISWA MATA PELAJARAN FIKIH KELAS IX DI MTS SWASTA JAM’IYAH MAHMUDIYAH TANJUNG PURA - Sri Wahyuni (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2024)
The results of this study show that: 1). The experimental class has a minimum value of 59 and a maximum value of 92, it is known that the average value is 73.55 with a standard deviation of 8.505. 2). The control class has a minimum value of 34 and a maximum of 77, an average of 61.59 with a standard deviation of 9.375. 3). The results of partial hypothesis testing with the significance or influence of the independent variable on the dependent variable. That the calculated T value (partial) for the questionnaire results is 5.901 with a significant level (2- tailed) of 0.000, then the Application of Ice Breaking has an effect on Student Learning Motivation in Jurisprudence subjects with a calculated T value of 5.901 > T table 1.671 and a significant value of 0.000 < 0.05 indicates that the Application of Ice Breaking has an effect on Student Learning Motivation in Jurisprudence Class IX at MTs Private Jam'iyah Mahmudiyah Tanjung Pura. This can be seen with a significant value (Sig.2- Tailed) 0.000 smaller than 0.05. So the research hypothesis Ha is accepted and H0 is rejected.